2020
DOI: 10.3390/microorganisms8050629
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Coagulase-Negative Staphylococci Diversity from Artisanal Llama Sausages: Assessment of Technological and Safety Traits

Abstract: Llama sausage is still produced following artisanal procedures, with the autochthonous microbiota being mainly responsible for the fermentation process. In this work, the taxonomical identification and technological-safety criteria of coagulase-negative staphylococci (CNS) isolated from two different productions of llama sausages (P: pilot and A: artisanal) were investigated. Staphylococcus (S) equorum and S. saprophyticus were the species most frequently found in P production, followed by S. succinis and S. w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
9
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 38 publications
5
9
1
Order By: Relevance
“…Among lactobacilli, more discrepancies were observed regarding to tetracycline phenotype/genotype, while a high number of ERY-R CNS resulted as genetically susceptible. This discordance between the phenotype and genotype was already reported by other authors [ 18 , 31 , 36 ] and may be explained by the presence of additional genes conferring resistance different than those investigated herein [ 20 , 34 , 37 ]. For example, many genes conferring tetracycline resistance were described, and among these, tet O, tet Q, tet 36, tet Z, tet O/W/32/O/W/O, tet W/O genes were also identified among lactobacilli [ 38 ].…”
Section: Resultssupporting
confidence: 65%
See 3 more Smart Citations
“…Among lactobacilli, more discrepancies were observed regarding to tetracycline phenotype/genotype, while a high number of ERY-R CNS resulted as genetically susceptible. This discordance between the phenotype and genotype was already reported by other authors [ 18 , 31 , 36 ] and may be explained by the presence of additional genes conferring resistance different than those investigated herein [ 20 , 34 , 37 ]. For example, many genes conferring tetracycline resistance were described, and among these, tet O, tet Q, tet 36, tet Z, tet O/W/32/O/W/O, tet W/O genes were also identified among lactobacilli [ 38 ].…”
Section: Resultssupporting
confidence: 65%
“…Resistance to relevant antibiotics has been already demonstrated for the bacterial strains under investigation as previously reported [ 11 , 12 , 18 , 22 ]. In this study, the same reference methods were used to assess the susceptibility to tetracycline and erythromycin of all L. sakei and L. plantarum and CNS isolates, in order to ensure a uniform approach and allow data comparison.…”
Section: Methodsmentioning
confidence: 57%
See 2 more Smart Citations
“…Our results recorded at the end of ripening were by 1 log CFU/g higher relative to comparison results, thus being inconsistent to the studies that found low coagulase-negative cocci counts in the final ripening stage [24]. According to some authors, the coagulase-negative cocci count varies depending on the sausage kind, ranging from 2 to 9 log CFU/g [30,35]. In our study, a total of 50 isolates of coagulase-negative cocci were isolated from sausages during ripening.…”
Section: Discussioncontrasting
confidence: 99%